Педагогічна підтримка адаптації молодших школярів до умов освітнього розвивального середовища - Дзеблюк, Юлія; Dzeblyuk, Yuliya (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена проблемі забезпечення педагогічної підтримки адаптації молодших школярів у період пристосування до умов освітнього розвивального простору. Визначені вікові характеристики дітей молодшого шкільного віку, особливості та концептуальні моделі розвивального навчання та провідні педагогічні засоби, які сприяють адаптації учнів початкової школи.The article is devoted the pedagogical support of adaptation of younger schoolchildren in the conditions of educational developing environment. During the initial stage of learning young schoolchildren have difficulties of the physiological, social and рsychological adaptation.Age features primary school children provide opportunities for success in school under the condition of overcoming barriers to this adaptation. There is an intensive intellectual development, the development of emotional and volitional at this age, which prepares a person to loads of educational activity, a change in social relations, an assimilation of rules of social interaction. The objective of the space of teaching schoolchildren is to create a positive climate and support the development of positive learning motivation, the formation of a class team in the period of adaptation of children. Also the teacher must actively engage with parents of pupils. We have conducted an empirical study of the pupils of the first class, including observation of teaching and non-learning activities, the survey of the pupils and parents, psychological study of cognitive processes. The determining factor for the successful adaptation of younger schoolboys is their personal readiness to learn.
The pedagogical support of the adaptation of younger schoolchildren in the conditions of educational developing environment
Keywords: адаптація; adaptation; соціально-педагогічна адаптація молодших школярів; педагогічні засоби; розвивальне педагогічне середовище; готовність до навчання; social-pedagogical adaptation of junior schoolchildren; pedagogical tools of primary school; developing educational environment; readiness to study at school